Fixed-Point Estimation by Iterative Strategies and Stability Analysis with Applications - Hammad, Hasanen A.; Kattan, Doha A. (Symmetry (Basel), 2023)
In this study, we developed a new faster iterative scheme for approximate fixed points. This technique was applied to discuss some convergence and stability results for almost contraction mapping in a Banach space and for Suzuki generalized nonexpansive mapping in a uniformly convex Banach space. Moreover, some numerical experiments were investigated to illustrate the behavior and efficacy of our iterative scheme. The proposed method converges faster than symmetrical iterations of the S algorithm, Thakur algorithm and K* algorithm. Eventually, as an application, the nonlinear Volterra integral equation with delay was solved using the suggested method.